2014
DOI: 10.3390/rs6031938
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Remote Sensing-Based “Boro” Rice Mapping System

Abstract: Rice is one of the staple foods across the world, thus information about its production is essential for ensuring food security. Here, our objective was to develop a method for mapping -boro‖ rice (i.e., cultivated during the months January to May) in a Bangladeshi context. In this paper, we used a Moderate Resolution Imaging Spectroradiometer (MODIS)-derived 16-day composite of normalized difference vegetation index (NDVI) at 250 m spatial resolution in conjunction with ancillary datasets (i.e., land use map,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 23 publications
3
34
0
Order By: Relevance
“…It would be interesting to note that the outcomes of the proposed method outperformed the earlier one. For example, the overall RE's were in the range ±10% using the proposed method in comparison to about ±30% using the method described in the earlier study (Mosleh & Hassan, 2014) (see Fig. 6 for details).…”
Section: Delineation Of Areas Under Rice Cultivationmentioning
confidence: 87%
See 2 more Smart Citations
“…It would be interesting to note that the outcomes of the proposed method outperformed the earlier one. For example, the overall RE's were in the range ±10% using the proposed method in comparison to about ±30% using the method described in the earlier study (Mosleh & Hassan, 2014) (see Fig. 6 for details).…”
Section: Delineation Of Areas Under Rice Cultivationmentioning
confidence: 87%
“…It revealed strong relations (i.e., R 2 in the range 0.93 to 0.95 and RMSE in the range 30,519 to 37,451 ha, at 23 district-levels) between modeled and ground-based area estimates. Our results were also similar to other studies: Panigrahy et al (1997) obtained accuracies in the range 85.8 to 91.5% in the early estimation of rice areas in Wet Bengal, India; (ii) Patel et al (2004) found approximately 95% accuracy in forecasting Kharif rice acreage in Orissa, India; (iii) Chen et al (2011) In addition, we also compared the boro rice area estimated using only two images acquired during the initial/transplantation and peak greenness stages in the scope of this paper with those extracted in an earlier study (Mosleh & Hassan, 2014). In that study, we employed ten 16-day composite of NDVI images acquired over the entire growing season and estimated the boro rice area after the harvesting of the crop.…”
Section: Delineation Of Areas Under Rice Cultivationmentioning
confidence: 99%
See 1 more Smart Citation
“…The PBIAS between the predicted yield showed a variation of less than ±10 per cent in 5 out of the 10 districts under study. This disagreements between the actual and predicted rice yield estimates could be attributed by other factors, such as atmospheric interference such as cloud (Mkhabela et al, 2011), micro level weather variation and water availability (Son et al, 2013) and uncertaininty associated with ground based estimates (Mosleh and Hassan, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…The ratios of the changes in amplitude of the LSWI to the two-band Enhanced Vegetation Index 2 (EVI2) during the period from the tillering to the heading stage were used as one indicator to discriminate rice from non-rice fields [26]. Mosleh and Hassan developed a method for mapping "Boro" rice in Bangladesh using the MODIS-derived 16-day composite NDVI at a spatial resolution of 250 m [27]. The ISODATA clustering and the formulation of the mathematical model were the key procedures of this algorithm.…”
Section: Introductionmentioning
confidence: 99%